Recent Advances in Studies of Molecular Hydrogen against Sepsis - Qiu, Peng (Int J Biol Sci, 2019)
Sepsis is a syndrome comprised of a series of life-threatening organ dysfunctions caused by a maladjusted body response to infection with no effective treatment. Molecular hydrogen is a new type of antioxidant with strong free radical scavenging ability, which has been demonstrated to be effective for treating various diseases, such as infection, trauma, poisoning, organ ischemia-reperfusion, metabolic diseases, and tumors. Molecular hydrogen exerts multiple biological effects involving anti-inflammation, anti-oxidation, anti-apoptosis, anti-shock, and autophagy regulation, which may attenuate the organ and barrier damage caused by sepsis. However, the underlying molecular mechanisms remain elusive, but are likely related to the signaling pathways involved. This review focuses on the research progress and potential mechanisms of molecular hydrogen against sepsis to provide a theoretical basis for clinical treatment.